2017
DOI: 10.1097/mcp.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of pleural effusions of multiple aetiologies

Abstract: Understanding that there are potentially concurrent causes to a pleural effusion is vital in establishing the diagnoses of multiple underlying aetiologies. New diagnostic pathways, with increasing use of biomarkers, will be required to identify the complex pleural effusion. Further studies on whether the targeting of separate aetiologies improves outcomes will help develop future management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…However, it is increasingly recognised that a significant proportion of patients presenting with a pleural effusion will have dual pathology driving their presentation and this bears consideration. In a prospective study of 126 patients with pleural effusion of unknown aetiology, 30% (38/126) were found to have more than one cause for their effusion, of which the commonest secondary cause was congestive cardiac failure [5,14].…”
Section: Pleural Fluidmentioning
confidence: 99%
“…However, it is increasingly recognised that a significant proportion of patients presenting with a pleural effusion will have dual pathology driving their presentation and this bears consideration. In a prospective study of 126 patients with pleural effusion of unknown aetiology, 30% (38/126) were found to have more than one cause for their effusion, of which the commonest secondary cause was congestive cardiac failure [5,14].…”
Section: Pleural Fluidmentioning
confidence: 99%
“…PE is related to more than 50 etiologies and could be divided into benign pleural effusion (BPE) and malignant pleural effusion (MPE) [ 7 ]. BPE is mainly caused by tuberculosis, pneumonia and chronic heart failure in China [ 8 ]. Sometimes, MPE presents as the initial or even only sign in patients with cancer, but this does not mean that MPE is a warning sign for early stage of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with known congestive cardiac failure (CCF) and bilateral effusions, it is highly likely that this is the cause of the effusions. 3 Unless there is a suspicion of dual pathologies, which are more common than previously thought, 4 diuresis should be undertaken rather than ABSTRACT Authors: Rachel M Mercer , A John P Corcoran , B Jose M Porcel , C Najib M Rahman D and Ioannis Psallidas E…”
Section: Introductionmentioning
confidence: 99%